Evaluasi Pembelajaran Membaca Permulaan Siswa Kelas Rendah di Sekolah Dasar - Magdalena, Ina; Ulyah, Emaliah Samhatul; Fitriya, Devi; Pujianti, Pujianti (YASIN, 2023)
This study aims to evaluate leraning to read Indonesian beginning in class II at Pondok Kacang Timur 03 Elementary School. This research uses a descriptive evaluation method with a qualitative approach. The data collected includes interviews with teachers and students, observation of evaluation activities. The results showed that the evaluation of early reading learning in the school used an outcome evaluation which consisted of formative and summative evaluations. Formative evaluation is carried out through oral tests, while summative evaluation is carried out through objective tests. Process evaluation is carried out t review the planning, implementation, and management of the learning process. Evaluation of students reading development is divided into process evaluation and product evaluation. Evaluation of learning outcomes inludes cognitive, affective, and psychomotor aspects. This study provides an overview of the evaluation of early reading learning in grade II at Pondok Kacang Timur Elementary School and can be used as a basis for improving the process of learning to read at that school.